Antiapoptotic activity of Chlamydia trachomatis Pgp3 protein involves activation of the ERK1/2 pathway mediated by upregulation of DJ-1 protein. Issue 9 (23rd January 2020) - Luo, Fangzhen; Shu, Mingyi; Gong, Silu; Wen, Yating; He, Bei; Su, Shengmei; Li, Zhongyu
ABSTRACT: Chlamydia trachomatis has evolved strategies to prevent host cell apoptosis to evade the host immune defense. However, the precise mechanisms of antiapoptotic activity of C. trachomatis still need to be clarified. Pgp3, one of eight plasmid proteins of C. trachomatis, has been identified to be closely associated with chlamydial virulence. In this study, we attempted to explore the effects and the mechanisms of Pgp3 protein on apoptosis in HeLa cells; the results showed that Pgp3 increased Bcl-2/Bax ratio and prevented caspase-3 activation to suppress apoptosis induced by TNF-α and cycloheximide (CHX) through ERK1/2 pathway activation. Downregulation of DJ-1 with siRNA-DJ-1(si-DJ-1) reduced ERK1/2 phosphorylation and elevated apoptotic rate significantly in Pgp3-HeLa cells. However, inhibition of ERK1/2 signal pathway with ERK inhibitor PD98059 had little effect on DJ-1 expression. These findings confirm that plasmid protein Pgp3 contributes to apoptosis resistance through ERK1/2 signal pathway mediated by upregulation of DJ-1 expression. Therefore, the present study provided novel insights into the role of Pgp3 in apoptosis and suggested that manipulation of the host apoptosis response could be a new approach for the prevention and treatment of C. trachomatis infection. Abstract : Pgp3 inhibits apoptosis via up-regulating DJ-1 expression and activating ERK1/2 pathway.